Analysis of Factors Affecting Regional Economic Growth from a Development Economics Perspective - Nurintan Asyiah (Yayasan Cinta Negara Indonesia, 2026)
Regional economic growth is one of the key indicators of development success and is influenced by various economic, social, and institutional factors. Differences in growth rates across regions highlight the need to analyze the factors that determine regional economic performance. This study aims to analyze the effects of investment, human capital quality, government spending, and infrastructure on regional economic growth from a development economics perspective. The study employs a quantitative approach using multiple linear regression analysis based on secondary data obtained from the Central Bureau of Statistics and relevant agencies. The results indicate that investment, human capital quality, and infrastructure have a positive and significant impact on regional economic growth, while government spending exerts a positive but relatively weaker influence. This study concludes that synergistic development policies focused on increasing investment, improving human resource quality, and developing infrastructure are key strategies for promoting sustainable regional economic growth